Chalcogen-atom transfer and exchange reactions of NHC-stabilized heavier silaacylium ions. Issue 46 (9th November 2017) - Sarkar, Debotra; Wendel, Daniel; Ahmad, Syed Usman; Szilvási, Tibor; Pöthig, Alexander; Inoue, Shigeyoshi
Abstract : Facile access to heavier silaacylium ions stabilized by two NHCs and their chalcogen transfer and exchange reactivity are reported. Abstract : Heavier analogues of silaacylium ions2–4 ([ m -TerSiE(NHC)2 ]Cl; m -Ter = 2, 6-Mes2 C6 H3 ; Mes = 2, 4, 6-Me3 C6 H2 ;2 (E = S), 3 (E = Se), 4 (E = Te)) were synthesized by the reaction of the NHC-stabilized silyliumylidene cation1 with elemental chalcogens. Fascinating regeneration of1 from the reaction of2–4 with AuI was achieved, as successful recovery of a parent Si(ii ) species from a silachalcogen Si(iv ) compound. Furthermore, unique chalcogen exchange reactions from 4 → 3 → 2 were observed in line with the calculated silicon–chalcogen bond energies.